Rational explanation of the relationship between the material intellect and the active intellect from the perspective of Averroes - Zandi, Davoud (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2015)
The relationship between the material intellect and the active intellect from Averroes’ perspective is an important and yet complicated part of his philosophy. His views on these issues are ambiguous since they are derived from the Aristotle’s theories which seem obscure in this regard. The aim of the present study is to discover Averroes’ final theory on the relationship between the material intellect and the active intellect and their connection to human soul. Reviewing various theories of Averroes on this issue, this study shows that despite ambiguity in his explanations, his final theory is that he believes these two intellects exist apart from human soul. Considering the relationship between the material intellect and the active intellect, he believes that in some aspects both of them are the same, yet they are different in some other aspects that is, regarding their acts, they are different because the active intellect acts as a creator of forms while the material intellect is just a receiver of the forms. Nevertheless, they are the same, since the material intellect achieves perfection through the active intellect.